ANALISIS PERBANDINGAN KINERJA REKSADANA SAHAM MENGGUNAKAN METODE SHARPE DAN TREYNOR PADA REKSADANA SAHAM - Bella, Clara; Permadhy, Yul Tito (EQUITY: Jurnal Ekonomi, Manajemen, Akuntansi, 2018)
This study aims to determine the comparison of stock mutual fund performance using sharpe method and treynor method. The research method used in this research is descriptive method with quantitative approach. The object of this study using all mutual fund shares listed on the Indonesia Stock Exchange period 2013-2016. The technique of determining the sample using purposive sampling method so that 66 mutual funds were chosen as research sample. The results of this study explain that there are differences in the results of the performance of stock mutual funds using sharpe method and treynor method on mutual fund shares listed on the Indonesia Stock Exchange (BEI) where each performance value fluctuates in the period 20132016. The results show that only a few stock mutual funds are above market performance by using sharpe method and treynor method during the period 2013-2016. The results show that only one stock mutual fund that has consistent performance above market performance during the period 2013-2016 using the sharpe method of equity fund Sam Equity Fund.